One-dimensional porous nanofibers of Co(3)O(4) on the carbon matrix from human hair with superior lithium ion storage performance - Tan, Yanli (Sci Rep, 2015)
One-dimensional (1D) hierarchical porous nanofibers of Co(3)O(4) possessing of (220) facets on the carbon matrix from human hair (H2@Co(3)O(4)) with 20–30 nm in width and 3–5 μm in length are prepared by a facile solvothermal and calcination approach. The well crystallized small Co(3)O(4) particles with the diameter of about 8–12 nm were closely aggregated together in the nanofibers. Electrochemical analyses show that the first discharge capacity of H2@Co(3)O(4) electrode is 1368 mAh g(−1) at the current density of 0.1 A g(−1) based on the total mass of composite. A high reversible capacity of 916 mAh g (−1) was obtained over 100 cycles at 0.1 A g(−1), presenting a good cycling stability. When cycled at a high current density of 1 and 2 A g(−1), the specific capacity of 659 and 573 mAh g(−1) could be still achieved, respectively, indicating a superior power capability.